2011
DOI: 10.1089/cbr.2010.0857
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein 4 Inhibits Cell Proliferation and Induces Apoptosis in Glioma Stem Cells

Abstract: Glioma stem cells (GSCs), which are originated from transformed neural stem cells, are tumor-initiating cells of glioma, the most common primary malignant neoplasm of the central nervous system. Extensive studies have shown that bone morphogenetic protein 4 (BMP4) plays an important role in the differentiation and proliferation of neural stem cells. To seek the functions and mechanisms of BMP4 in GSCs, GSCs isolated from U87 human glioma cells by using vincristine were exposed to BMP4 protein. This study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Zhou et al [24] observed that BMP4 may act as a key inhibitory regulator of cancer initiation and therefore may be used in combined stem cell-based therapy as a noncytotoxic therapeutic agent. The CD133+ GIC fraction used in this study was isolated from the human glioma cell line U87 by using vincristine and was exposed to the BMP4 protein.…”
Section: Bmp Effects On Glioma Initiating Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al [24] observed that BMP4 may act as a key inhibitory regulator of cancer initiation and therefore may be used in combined stem cell-based therapy as a noncytotoxic therapeutic agent. The CD133+ GIC fraction used in this study was isolated from the human glioma cell line U87 by using vincristine and was exposed to the BMP4 protein.…”
Section: Bmp Effects On Glioma Initiating Cellsmentioning
confidence: 99%
“…As we explained above, BMPs have been shown to promote GIC differentiation and to reduce GBM proliferation in vitro and in vivo [23, 24, 2931, 38], so they are becoming promising therapeutic tools that could be used in combination with other conventional treatments (Figure 1). This has been recently explored by several groups.…”
Section: Bmps As Therapeutic Targets In Astrocytic Gliomamentioning
confidence: 99%
“…[1][2][3][4][5][6] Regarding the effect of BMP4 on tumors, BMP4 was shown to induce differentiation in CSCs and suppress tumor growth in glioblastoma and colon cancer. 4,5 Zhou et al 7 reported that BMP4 inhibited proliferation and induced apoptosis in glioma stem cells. Because BMP4 is originally expressed in the neural crest during the development of the embryo, 8 it may play a particular role in the regulation of neural cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…BMPs have been either inhibitory or stimulatory in central nervous system-associated tissues. BMP4 inhibits glioma stem cell proliferation (Zhou et al, 2011;Kallionemi, 2012) but stimulates pituitary adenoma cells and inhibits primitive neuroectodermal cell apoptosis (Intoska, et al, 1999;Paez-Pereda et al, 2003,). BMP4 stimulation of other select mesodermal and epithelial cells has also been described (Yang et al, 2007, Montesano et al, 2008.…”
Section: D Bmp Regulation Of Proliferation In Neoplasia Including Mmentioning
confidence: 99%